Pengaruh Karakteristik Perusahaan Terhadap Nilai Perusahaan dengan Struktur Modal Sebagai Variabel Intervening - Meli Meli (Jurnal Ekonomi, 2020)
This study aims to examine the effect of Profitability (ROE), Asset Structure (FAR), Firm Size (SIZE), Firm Age (AGE) and Capital Structure (DER) on Firm Value (Tobin's Q). This research is in addition to knowing the direct and indirect effect of Capital Structure as a connecting variable between Profitability, Asset Structure, Company Size, Company Age on Firm Value. This study uses a sample of 40 manufacturing companies listed on the Indonesia Stock Exchange with a five-year period, namely 2013-2017 and a total sample of 200 companies. This study uses data collection techniques with the documentation method from the official website of the Indonesia Stock Exchange and Sahamok. The data in this study used panel data, and tested the intervening variables with SEM (Structural Equation Model). The results of this study explain that profitability has an influence on firm value, asset structure has no effect on firm value, firm age has an influence on firm value, firm size has an influence on firm value, firm characteristics through profitability have an influence on capital structure, while asset structure, age and size of the company have no effect on the capital structure. Capital structure is not able to mediate the characteristics of the company to the value of the company